The Universal Form of the Singular: The Early Philosophy of Ernst Cassirer (1898-1917) - Esparza, Gustavo, (New Research in the History of Western Philosophy ;, 2025)
This book examines the philosophical foundations on which Cassirer bases the central themes of his thought, namely function and the symbolic, establishing as the core inquiry the way in which knowledge of the singular is made possible. Through an exploration of works published between 1898 and 1917, it is argued that knowledge is constituted as a relationship between unity and a general form that enables the designation of a phenomenon as an object of knowledge. The justification that the universal is the foundation of the singular can be achieved through Cassirer's philosophy, while also providing a fundamental reason for studying his early philosophical period.